Immobilization of uranium(VI) by niobate/titanate nanoflakes heterojunction through combined adsorption and solar-light-driven photocatalytic reduction - Xiaona Liu; Du, Penghui; Weiyi Pan; Dang, Chenyuan; Qian, Tianwei; Liu, Hongfang; Liu, Wen; Zhao, Dongye (Applied Catalysis B: Environmental, 2018)
Abstract A niobate/titanate nanoflakes (Nb/TiNFs) composite was synthesized through a one-step hydrothermal method. Nb/TiNFs displayed a heterojunction structure owing to deposition of a small fraction of niobate onto tri-titanate nanoflakes. Tri-titanate (Na1.6H0.4Ti3O71.7H2O) was the primary crystal phase, and the molar ratio of niobate (Na2Nb2O6H2O) to titanate was determined to be 1:15.9. Nb/TiNFs showed rapid adsorption kinetics and high adsorption capacity for U(VI) (Langmuir Qmax = 298.5 mg/g). Ion-exchange and surface complexation were the key mechanisms for U(VI) uptake, and the adsorption was further enhanced by the unique tunnel lattice structure of the heterojunction. Moreover, Nb/TiNFs were able to convert U(VI) into its immobile form, UO2(s) under solar light through photocatalytic reduction. More than 89.3% of (VI) was transformed into U(IV) after 4 h of solar irradiation (initial U(VI) = 20 mg/L, pH = 5.0). Diffuse reflectance UV–vis absorption spectra and Mott-Schottky plots indicated a narrowed band gap energy of Nb/TiNFs compared to neat TNTs. Density functional theory (DFT) calculation on band structure and density of states further confirmed the heterojunction architecture of niobate and titanate, resulting in offset of the conduction bands for the two phases in the composite material. Therefore, transfer of photo-excited electrons from titanate to niobate leads to inhibition of recombination of the electron-hole pairs. In addition, the trapping of uranium in the tunnel lattice of titanate and niobate heterojunction prevents re-oxidation of U(IV) to U(VI), thus achieving long-term immobilization of uranium. Remobilization tests indicated that only 18.7% of U(VI) was re-oxidized to U(VI) and almost no U dissolved into the aqueous phase when exposed air for 90 days. The new material is promising for separation and safe disposal of high strength radionuclides in water.
Keywords: Photocatalytic reduction